Impact of blue economy sectors using causality, correlation and panel data models - Martínez-Vázquez, Rosa María; Milán-García, Juan; Pires Manso, Jose Ramos; De Pablo Valenciano, Jaime (Frontiers in Marine Science, 2023)
This study aims to investigate the causal relationships between blue economy factors such as living and non-living resources, ocean energy, port activities, shipbuilding and repair, maritime transport, coastal tourism, human development indicator, per capita income, fish capture, internal renewable water resources per capita, marine protected areas, greenhouse gas emissions and population density, mostly related to maritime activities and the blue economy using some special analytical methods. The data used for these studies were collected from the Eurostat database and cover several European countries and the period 2010-2018. This study uses Granger’s theory of multivariate causality, correlation analysis methods and panel data techniques to study the complex web of relationships among various factors related to the blue economy and their influence on per capita income growth. The analysis showed evidence that per capita income is related to other factors of the blue economy, that per capita income (Granger) causes coastal tourism and population density, and that there are five other factors that positively influence per capita income growth, namely, GHG, maritime transport, non-living resources and port activities. If policymakers want to increase the per capita income of these regions, they should act on some variables such as HDI, GHG emissions, living resources, maritime transport and ocean energy. The results reveal that blue economy is a good alternative to promote growth, both economic and per capita income. The known factors that make up the blue economy, such as ocean energy, port activities, shipbuilding and repair, maritime transport, coastal tourism, the human development indicator, maritime fish capture, marine protected areas, and the reduction of greenhouse gas emissions are good factors to stimulate economic growth. This study innovates in the methods and techniques used, in the results discovered and in the combination of blue economy factors. It is the first paper to address the impacto of blue economy, filling a gap in literature.